Analysis of morphology and population dynamics of giant mudskipper Periophthalmodon schlosseri (Gobiiformes: Oxudercidae) at Sungsang Estuaries, South Sumatra, Indonesia - MELKI MELKI; FADHILAH DZAKIYYAH ANANTA; ISNAINI ISNAINI; FITRI AGUSTRIANI; REZI APRI; HARTONI HARTONI; ELLIS NURJUALISTI NINGSIH; JENI MEIYERANI (Society for Indonesian Biodiversity, 2025)
Abstract. Melki, Ananta FD, Isnaini, Agustriani F, Apri R, Hartoni, Ningsih EN, Meiyerani J. 2025. Analysis of morphology and population dynamics of giant mudskipper Periophthalmodon schlosseri (Gobiiformes: Oxudercidae) at Sungsang Estuaries, South Sumatra, Indonesia. Biodiversitas 26: 2269-2277. The giant mudskipper Periophthalmodon schlosseri is one of the most abundant mudskipper species, playing a vital role in the biomass of mangrove ecosystems. Mudskipper fish are also found in the Sungsang Coast, an estuary of the Musi River that is fed by river water from three provinces in Indonesia: South Sumatra, Lampung, and Bengkulu. This study aimed to analyze the morphology and population dynamics of mudskippers along with their environmental parameters in Sungsang Coastal, South Sumatra. For this study, mudskipper specimens were collected from five sampling sites along the Sungsang Coast and analyzed for morphometric characteristics, length-weight relationships, and their correlations with key environmental parameters like temperature, pH, and dissolved oxygen. The analysis of fifty-five specimens revealed an average total length of 20.08 cm, a standard length of 17.34 cm, and an average weight of 85.4 g. The growth pattern exhibited positive allometry (b>3), suggesting that as these fish grow, their body weight increases faster than their length. Condition factor analysis indicated that the fish sampled were healthy and in good nutritional condition. The Principal Component Analysis (PCA) further highlighted a strong association between dissolved oxygen and pH levels with the morphometric characteristics of the mudskippers, explaining 55.47% of the variation on the F1 axis and 24.70% on the F2 axis. This robust correlation between environmental factors and morphometric characteristics underscores the reliability of our findings. These findings provide crucial insights into the ecological health of the Giant Mudskipper and its dependence on specific environmental factors in the mangrove habitat are of utmost importance.